PENGARUH KOMPENSASI, KEPEMIMPINAN DAN DISIPILIN KERJA TERHADAP KINERJA KARYAWAN PT PERKEBUNAN HIJAU PRAYAN PERDANA - Broto, Bayu Eko (LPPM Universitas Labuhanbatu, 2021)
This research was conducted at PT Perkebunan Green Prayan Prime, where this type of research is quantitative research. This study aims to determine the compensation, leadership and work discipline simultaneously influence on the performance of employees at PT Perkebunan Green Prayan Prime. Based on the data obtained by the researchers of the 59 respondents who processed through the stages of scientific and also analyzed through the stages according to the rules of research by testing, were summed up that the calculation Results obtained for the variable Compensation (X1) with a significance of 0, 595 showed that the value is smaller than 0.05 and t 0,536 < 1,677 ttable. The calculation results obtained for the variable Leadership (X2) with a significance less than 0.001 to indicate that the value is smaller than 0.05 and t 3,718 > ttable 1,677. The calculation results obtained for the variable Work Discipline (X3) with a significance of 0.000 indicates that the value is smaller than 0.05, and the value of tcount 3,949 > ttable 1,677. Using a significance level of 0.05, then the value of significance F of 0.000 indicates less than 0.05, and the value of Fcount 10,463 > Ftable of 2.79. So the hypothesis that there is significant influence between the independent variable Compensation (X1), Leadership (X2), and Work Discipline (X3) simultaneously to variable tied to Employee Performance (Y) can be received.